Bioscience learning in nursing: a cross-sectional survey of beginning nursing students in Norway - Aud Emelie Evensen; Hildfrid Vikkelsmoe Brataas; Guanglin Cui (BMC, 2020)
Abstract Background Taking bioscience courses such as anatomy and physiology (A&P) is important for the development of nursing competence, but learning such subjects is also a challenge for many students. Nursing students' motivation, academic performance and exposure to different teaching methods may influence the learning process. Methods A descriptive survey was conducted with first-year nursing students at a university in Central Norway to explore their motivations, academic performance, and responses to various teaching methods used in an A&P course. Results The study provided insight into nursing students motivation, academic performance, and responses to various teaching approaches. 57 students participated in the survey and 91 % of them passed the course. The majority (61.4%) reported that classroom lecture was the most efficient and appreciated teaching method. Independent study was significantly associated with higher A&P exam grades (p-value < 0.05). Conclusion The survey suggests a need for further research about the quality, and presentation of anatomy and physiology units.